2009
DOI: 10.1159/000210449
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component and Linkage Analysis of Cardiovascular Risk Traits in the Norfolk Isolate

Abstract: Objective(s): An individual’s risk of developing cardiovascular disease (CVD) is influenced by genetic factors. This study focussed on mapping genetic loci for CVD-risk traits in a unique population isolate derived from Norfolk Island. Methods: This investigation focussed on 377 individuals descended from the population founders. Principal component analysis was used to extract orthogonal components from 11 cardiovascular risk traits. Multipoint variance component methods were used to assess genome-wide linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 101 publications
2
22
0
Order By: Relevance
“…Notably, there was no difference in the mean MSE between Pitcairn and non‐Pitcairn populations 18 . To date, the Norfolk Island population has been a very useful population in which to study the genetic epidemiology of cardiovascular traits, 40,41 and it is hoped will yield significant discoveries in ophthalmic genetics and epidemiology. Indeed there is considerable evidence suggesting an inheritable contribution to the aetiology of refractive error, 42 as well as in the biometric components that are associated closely with the presence and development of refractive error 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, there was no difference in the mean MSE between Pitcairn and non‐Pitcairn populations 18 . To date, the Norfolk Island population has been a very useful population in which to study the genetic epidemiology of cardiovascular traits, 40,41 and it is hoped will yield significant discoveries in ophthalmic genetics and epidemiology. Indeed there is considerable evidence suggesting an inheritable contribution to the aetiology of refractive error, 42 as well as in the biometric components that are associated closely with the presence and development of refractive error 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the people with two eyes available (n = 538), all-age prevalence of anisometropia (inter-eye difference Ն 1.0 D) was 14.8%. Prevalence in people aged 15-29 was 5.5%, in people aged 30-39 was 10.0%, 5.7% in people aged [40][41][42][43][44][45][46][47][48][49]11.6% in people aged 50-59, 16.4% in people 60-69, and rising to 34.8% in people aged 70 and over. Prevalence in women was 11.9%, and in men 14.8%.…”
Section: Anisometropiamentioning
confidence: 99%
“…Presently, principal component factor analysis (PCFA) has been used to extract independent factors from large amount of inter-correlated factors [1,11,12] . The PCFA is a statistical method of data reduction which has been used in past many years to identify the clustering of risk factors of the metabolic syndrome [1,2,11,13] . All these studies have consistently found multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…PCA was used to derive quantitative phenotypes and CA to identify phenotypically homogenous groups of individuals. PCA and CA have been used effectively to develop well defined phenotypes for genetic mapping of complex traits such as cardiovascular disease (Cox, Bellis et al 2009) and schizophrenia (Lin, Liu et al 2009).…”
Section: Discussionmentioning
confidence: 99%